Jürgen Habermas: Faktizität und Geltung - Guibentif, P. (Soziologische Theorien des Rechts: Eine Einführung anhand von Schlüsseltexten, 2024)
Discussion of the book of Jürgen Habermas, Faktizität und Geltung (Between Facts and Norms) (1992), the context in which it was written, its place in the work of the author, its argument, its reception, and possible developments.